Design, Development and Characterization of Verapamil Hydrochloride Pulsincap: In Vitro and In Vivo (Asian Journal of Pharmaceutics (AJP), 2025)
In this present study, design and development, of pulsatile capsule for the timed release of verapamilhydrochloride (HCl), utilizing the pulsincap method for irregular heartbeats. Materials and Methods: Usinghydroxy propyl methyl cellulose (HPMC), E15 sugar spheres were sealed. The verapamil HCl was sprayed onsugar spheres using Fluidized Bed (bottom spray) technology. By using FBP HPMC E15 and polymeric solutionof cross-Carmellose Sodium also coated a layer on sugar spheres. The formaldehyde-treated 0-sized capsules filledwith coated pellets and sealed with 1:1 of HPMC K4 and lactose as a plug. Results and Discussion: The EudragitL100 was used to release the drug in an extended release. The in vitro drug release was conducted using pH 7.4phosphate buffer for 17 h with the cumulative percentage release from 99.827%. The formulation V7, whichdemonstrated 99.827% drug release at 17 h with a 5-h lag time, was identified as the optimized formulation. Thein vivo Pharmacokinetic and dynamic studies were conducted in the rabbit model and estimated. The Cmax54.62± 0.42 ng/mL, t1/2 8.54 ± 0.013 h, and AUC0-α 944.8 ± 2.07 ng/mL. It was observed that there is a significantdifference (P < 0.05) between the pharmacokinetic parameters of the oral solution and pellets of verapamil HCl.Conclusion: A significant lag time of V7 is shown in plasma concentration when compared with the oral solution.The formulation has successfully demonstrated programmed pulsatile release over a 12-h period, aligning with therequirements of Pulsincap drug delivery.